PPAR-γ Signaling Crosstalk in Mesenchymal Stem Cells - Ichiro Takada; Alexander P. Kouzmenko; Shigeaki Kato (PPAR Research)
Peroxisome proliferator-activated receptor-gamma (PPAR-γ) is a member of the nuclear receptor (NR) superfamily of ligand-activated transcriptional factors. Among other functions, PPAR-γ acts as a key regulator of the adipogenesis. Since several cytokines (IL-1, TNF-α, TGF-β) had been known to inhibit adipocyte differentiation in mesenchymal stem cells (MSCs), we examined the effect of these cytokines on the transactivation function of PPAR-γ. We found that the TNF-α/IL-1-activated TAK1/TAB1/NIK (NFκB-inducible kinase) signaling cascade inhibited both the adipogenesis and Tro-induced transactivation by PPAR-γ by blocking the receptor binding to the cognate DNA response elements. Furthermore, it has been shown that the noncanonical Wnts are expressed in MSCs and that Wnt-5a was capable to inhibit transactivation by PPAR-γ. Treatment with Wnt5a-activated NLK (nemo-like kinase) induced physical association of the endogenous NLK and H3K9 histone methyltransferase (SETDB1) protein complexes with PPAR-γ. This resulted in histoneH3K9 tri-methylation at PPAR-γ target gene promoters. Overall, our data show that cytokines and noncanonical Wnts play a crucial role in modulation of PPAR-γ regulatory function in its target cells and tissues.